Meningkatkan Kemampuan Pengurangan Deret ke Bawah Melalui Model Pembelajaran Tutor Sebaya bagi Anak Diskalkulia - Riska Fitri Amelia; Asep Ahmad Sopandi (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This study consists of two cycles where each cycle consists of four meetings consisting of four stages of the process, namely planning, action, observation, and reflection. The data obtained through observation and tests of deeds are analyzed qualitatively and quantitatively. From the results of the study found that the reduction of the series down with the application of the peer tutor learning model can improve student's ability. Results obtained from the initial ability of students is HM with a value of 60; ARR 72,5; FEF 65; SM 82,5; and AV with a value of 77,5. It can be concluded that the application of the peer tutor learning model can improve the ability of the reduction of the series down with the technique of borrowing on third grade dyscalculia children in SDN 44 Sungai Lareh Padang.